Purificación Del Aire Ambiente Interior En La Fábrica De Productos Lácteos “Quesos Latacunga” , Cotopaxi, Ecuador - Agustín Leiva Pérez; Ely F. Sacón Vera; Rodolfo Najarro Quintero; Azucena Elizabeth Bernal; David W. Moreira Vega; Joffre A. Andrade Candell (European Scientific Journal, ESJ, 2017)
The purification of the internal ambient air of the "Latacunga Cheese" factory was studied by the application of ozone. It is an energetic oxidizing agent which is able to kill the microorganisms present in the medium where it is found. It is applied in its appropriate doses with the aim of purifying the air environment of the workshop. The concentrations of fungi and bacteria found before the application of ozone were higher than that allowed by the Spanish legislation "UNE 100012 Hygiene of systems". Among the fungi identified were Aspergillus sp., Penicilium sp., Scopulariopsis sp., Fusarium sp., and Cladosporium sp. The major bacteria identified were Staphylococcus sp., Streptococcus sp., Bacillus sp., Streptomyces sp., and Enterobacter agglomerans. The main material used for the treatment of indoor air with ozone was a SEFILTRA purifier. This purifier, however, generates an ozonated air flow rate of 2 dm3 / min with an ozone concentration in air of 9.5 g / m3. This means it has an ozone charge of about 1.14 g / hr. A High Efficiency Particle Arresting (99.995%) filter was used to measure microbial air content before and after treatment. After an hour of application of ozone, the reduction of fungi was sufficient to ensure that its presence was complied with the maximum limit established in the legislation in question. However, this does not happen with bacteria which needs about 25 minutes more to conclude which is the same as for fungi.